Hydrogen atom abstraction mechanism for organic compound oxidation by acetylperoxyl radical in Co(II)/peracetic acid activation system - Du, Penghui; Junjian Wang; Guodong Sun; Long Chen; Liu, Wen (Water Research, 2022)
Peracetic acid (PAA) has been widely used as an alternative disinfectant in wastewater treatment, and PAA-based advanced oxidation processes (AOPs) have drawn increasing attention recently. Among the generated reactive species after PAA activation, acetylperoxyl radical (CH3CO3•) plays an important role in organic compounds degradation. However, little is known about the reaction mechanism on CH3CO3• attack due to the challenging of experimental analysis. In this study, a homogeneous PAA activation system was built up using Co(II) as an activator at neutral pH to generate CH3CO3• for phenol degradation. More importantly, reaction mechanism on CH3CO3•-driven oxidation of phenol is elucidated at the molecular level. CH3CO3• with lower electrophilicity index but much larger Waals molecular volume holds different phenol oxidation route compared with the conventional •OH. Direct evidences on CH3CO3• formation and attack mechanism are provided through integrated experimental and theoretical results, indicating that hydrogen atom abstraction (HAA) is the most favorable route in the initial step of CH3CO3•-driven phenol oxidation. HAA reaction step is found to produce phenoxy radicals with a low energy barrier of 4.78 kcal mol−1 and free energy change of -12.21 kcal mol−1. The generated phenoxy radicals will undergo further dimerization to form 4-phenoxyphenol and corresponding hydroxylated products, or react with CH3CO3• to generate catechol and hydroquinone. These results significantly promote the understanding of CH3CO3•-driven organic pollutant degradation and are useful for further development of PAA-based AOPs in environmental applications.
Keywords: Acetylperoxyl radical; Advanced oxidation process; Hydrogen atom abstraction; organic compound; Peracetic acid